2006
DOI: 10.1089/ten.2006.12.45
|View full text |Cite
|
Sign up to set email alerts
|

Gravity Spun Polycaprolactone Fibers for Applications in Vascular Tissue Engineering: Proliferation and Function of Human Vascular Endothelial Cells

Abstract: Poly(epsilon-caprolactone) (PCL) fibers produced by wet spinning from solutions in acetone under lowshear (gravity-flow) conditions resulted in fiber strength of 8 MPa and stiffness of 0.08 Gpa. Cold drawing to an extension of 500% resulted in an increase in fiber strength to 43 MPa and stiffness to 0.3 GPa. The growth rate of human umbilical vein endothelial cells (HUVECs) (seeded at a density of 5 x 10(4) cells/mL) on as-spun fibers was consistently lower than that measured on tissue culture plastic (TCP) be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 29 publications
(32 reference statements)
0
21
0
Order By: Relevance
“…Gelatine has also been used [26], presumably as a low cost alternative source of soluble collagen. Collagen and gelatine generally favour the attachment, proliferation and retention of cells and, hence, they have been used in several studies to coat other materials used for scaffolds, such as polycaprolactone [27].…”
Section: Introductionmentioning
confidence: 99%
“…Gelatine has also been used [26], presumably as a low cost alternative source of soluble collagen. Collagen and gelatine generally favour the attachment, proliferation and retention of cells and, hence, they have been used in several studies to coat other materials used for scaffolds, such as polycaprolactone [27].…”
Section: Introductionmentioning
confidence: 99%
“…Gelatin coating of PCL fibers has previously been shown to improve fibroblast proliferation by a factor of 2 after 48 h in cell culture. 31 The data in Fig. 9 also indicates that a macropore size of 90-125 lm is advantageous for fibroblast growth on macroporous PCL materials.…”
Section: Resultsmentioning
confidence: 79%
“…Similar behavior was observed previously for 3T3 mouse fibroblasts cultured on PCL fibers. 31 Cell numbers were generally higher by a factor of two on macroporous PCL at day 5 and 8 compared with microporous material. However, the macroporous component is not anticipated to influence the number of attached cells due to the low macropore density at the material surface (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Using 3D image data acquired using methods describe here and in previous works [64,65,67], we have shown that CAD tools can produce models designed for use in computer aided manufacturing (CAM) of tissue scaffolding ( Figure 6), not only for capillary bed systems and their connecting vasculature (Figure 1) [65], but to replicate as imaged from a sample from a specific organ system and manufacture using CAM a structural representation of unique cellular boundaries for specific tissue structures (Figures 5&6).…”
Section: Discussionmentioning
confidence: 99%